Risk Taking Propensity and Firm Internationalisation Process - Janusz Fudaliński (Entrepreneurial Business and Economics Review, 2015)
Objective: The aim of this paper is to present necessary characteristics of solutions related to risk management in the conditions of high environment turbulence from the perspective of international businesses.